A comprehensive critique of student evaluation of teaching : critical perspectives on validity, reliability, and impartiality - Clayson, Dennis E. (New York, NY : Routledge, 2021)
"This thought-provoking volume offers comprehensive analysis of contemporary research and literature on student evaluation of teaching (SET) in Higher Education. In evaluating data from fields including education, psychology, engineering, science, and business, this volume critically engages with the assumption that SET is a reliable and valid measure of effective teaching. Clayson navigates a range of cultural, social, and era-related factors including gender, grades, personality, student honesty, and halo effects to consider how these may impact on the accuracy and impartiality of student evaluations. Ultimately, he posits a "popularity hypothesis", asserting that above all, SET measures instructor likability. While controversial, the hypothesis powerfully and persuasively draws on extensive and divergent literature to offer new and salient insights regarding the growing and potentially misleading phenomenon of SET. This topical and transdisciplinary book will be of great interest to researchers, faculty, and administrators in the fields of higher education management, administration, teaching and learning"--
Issues and debates surrounding student evaluations of teaching -- Potential impacts of gender bias on student evaluations -- The influence of personality traits on student evaluations -- Halo effects impacting on student evaluations -- Questioning the truthfulness of student evaluations -- Rigor, grades and how they impact on student evaluations -- The association between student learning and student evaluations -- Student evaluations and the improvement of instruction -- Challenging the statistical reliability of student evaluations -- Traditional validity and SET -- Identifying valid applications of SET -- Validity and the impacts of subjectivity -- Introducing a likability hypothesis -- Justifications of the likability hypothesis -- Conclusion and recommendations : the future of SET.
"Routledge Focus" -- taken from front cover.
OCLC-licensed vendor bibliographic record.
Keywords: College teachers -- Rating of; College teaching -- Evaluation; Student evaluation of teachers; EDUCATION / Evaluation; EDUCATION / Higher; EDUCATION / Testing & Measurement